Teacher Training for Pupils’ Sexuality Education in Lithuania: An Evaluation of Study Programmes and the Preparedness of Students of Pedagogical Studies - Bytautas, Marius; Daukilas, Sigitas (Pedagogika, 2023)
The paper presents findings from an evaluative mixed-methods study on teacher training for sexuality education in Lithuania. The analysis of the course outlines of pedagogical studies has identified the scope of preparation for sexuality education, the topics of the content presented, and a typical programme of preparation for sexuality education. Based on the data from the survey of students and graduates, conclusions about their readiness to carry out sexuality education were formulated.